Care coordination in Health Care for the child/adolescent in chronic condition - Elenice Maria Cecchetti Vaz; Neusa Collet; Emília Gallindo Cursino; Franklin Dellano Soares Forte; Rafaella Karolina Bezerra Pedrosa Magalhães; Altamira Pereira da Silva Reichert
ABSTRACT Objective: To analyze the care coordination for the child and adolescent in chronic condition and users planning in the Health Care Network. Method: Qualitative study, conducted with 26 health professionals and managers through Focus Groups. Thematic content analysis was used. Results: Care coordination is fragile, with lack of support from the management, and presence of high turnover of managers and professionals. The limits in the network planning are due to frequent changes in the careflow. Communication between levels of care and lack of counter-referral makes network care unfeasible. Final considerations: There is a need for planning in the Health Care Network and establishment of careflow, as well as the construction of communication channels and tools of referral and counter-referral between professionals and services, for the constitution and integration of the network from the perspective of user-centered care.